Ultrafast hot-electron injection at HfN-metal oxide heterojunctions: Role of barrier height - Singh, Ranveer; Sial, Qadeer Akbar; Kim, Unjeong; Nah, Sanghee; Seo, Hyungtak (Materials Science in Semiconductor Processing, 2022)
The concept of hot carrier-based solar cell is suggested for high-efficiency photovoltaics by overcoming thermodynamic limit of conversion efficiency. However, efficiency is largely affected by the quality of absorber materials and dynamics of hot carriers (HCs) in the same. Here, we demonstrate the generation of HCs and their transfer dynamics to the metal oxides by performing the femtosecond transient absorption spectroscopy measurements. The role of oxygen composition/content is highlighted on the different physical properties of hafnium nitride (HfN) thin films because the presence of oxygen in HfN deteriorates/quenches the HC generation. All HfN thin films exhibit the polycrystalline nature and the degree of crystallinity decreases with increasing the oxygen concentration as confirmed by X-ray diffraction and high-resolution transmission electron microscopic studies. In addition, the absorption measurements exhibit the broadband light absorption efficiency of the HfN films. The transient absorption maps show a strong photobleaching signal over a wide spectral range. The transient bleach dynamics probed at 650 nm show the faster decay rate (0.77 ps) for the HfN/TiOx in comparison to HfN (1.5 ps) and HfN/MoOx (3.7 ps), revealing the efficient electron transfer from HfN to TiOx layer. These results advance our understanding of hot-electron dynamics in HfN-oxide heterostructures and offers to design an ultra-fast optoelectronics device of HCs.
Keywords: Barrier heights; Hafnium nitride films; Hafnium nitrides; Hot electron injection; Hot-carriers; Kelvin probe force microscopy; Metal-oxide; TiO; Transition metal nitrides; Ultra-fast; HfN films; Hot carriers; Kelvin probe force microscopy; Optoelectronic; Transition metal nitrides; Work function